A APROPRIAÇÃO DA VIDA: Roger Chartier e uma leitura do mundo - Costa, João Paulo P. (Outros Tempos: Pesquisa em Foco - História, 2011)
From the works of French historian Roger Chartier,  as well as my personal experiences with hiswritings, we intend this article to analyze the arguments and ideas developed by this author in relation to the actof reading. Based on their studies on the history of books and reading itself, we could see not only the characterof "indiscipline" that involves the actions of the players throughout history, but also a strong connection of thisresearcher with intellectual’s production of Michel de Certeau. Through these dialogues, I could also, in my ownhistorical research on colonial Indians in Ceara, "delinquency" my reading of Chartier, and thus, to relate the actof reading studied by the author with the way indigenous peoples perceive, from in particular, the "new world"that was configured around them.